Comparison of Maternal Ophthalmic Artery Doppler Parameters in Gestational Hypertensive and Normotensive Pregnant Women: A Cross-sectional Study - Prashansa Gupta; Himadri Bal; Col Yoginder Singh; Tushar Pancholi; Priyanka Aher; Janvi Patel; Varshini Vadithala (Journal of Clinical and Diagnostic Research)
Introduction: Hypertensive disorders of pregnancy, including gestational hypertension and preeclampsia, significantly contribute to maternal and perinatal morbidity. Identifying early vascular changes through non invasive methods is crucial for improving risk stratification and clinical outcomes. Aim: To compare the ophthalmic artery Doppler parameters in gestational hypertensive and normotensive pregnant women. Materials and Methods: A cross-sectional study was conducted in the of Department of Obstetrics and Gynaecology at Dr. D.Y. Patil Medical College, Hospital, and Medical Research Centre, Pimpri, Pune, Maharashtra, India, from September 2023 to March 2025. A total of 450 primigravida and second-gravida women between 30 and 37 weeks of gestation, with confirmed gestational age based on first or early second-trimester ultrasonography, were included in both the gestational hypertension (n=80) and normotensive groups (n=370). Doppler ultrasound assessed key ophthalmic artery parameters, including the first and second Peak Systolic Velocities (PSV), the Peak Ratio (PR), and the Pulsatility Index (PI). Statistical analysis was performed to compare Doppler indices between the groups using appropriate statistical tests. Results: The mean maternal age was 29.4±5.7 years. The first and second PSVs were significantly elevated in hypertensive pregnancies (p<0.001). The PR was also significantly higher in hypertensive pregnancies (p<0.001), suggesting altered arterial compliance. While one PI parameter (PI-C) was significantly elevated (p<0.001), other PI values did not show significant differences. Conclusion: Ophthalmic artery Doppler parameters, mainly first and second PSVs and PR, serve as promising non invasive markers for hypertensive disorders in pregnancy.